The Efficacy and Safety of Remimazolam Tosilate Versus Dexmedetomidine in Outpatients Undergoing Flexible Bronchoscopy: A Prospective, Randomized, Blind, Non-Inferiority Trial - Chen, Xingfang; Xin, Deqian; Xu, Guangjun; Zhao, Jing; Lv, Qing (Frontiers in Pharmacology, 2022)
Purpose: This study aimed to compare the efficacy and safety of remimazolam tosilate-remifentanil (RT-RF) vs dexmedetomidine- remifentanil (Dex-RF) for outpatients undergoing fiberoptic bronchoscopy (FB). Patients and methods: We conducted a double-blind, randomized, prospective study involving a total of 146 outpatients undergoing FB divided into two groups. The RT-RF (RR) group (n=73) received an initial dose of 12 mg/kg/h of RT for 10 min followed by a maintenance dose of 1–2 mg/kg/h, while the Dex-RF (DR) group (n=73) received an initial dose of 0.5 µg/kg of Dex for 10 min followed by a maintenance dose of 0.2–0.7 µg/kg/h. All outpatients also received 0.05–0.2 µg/kg/min RF to maintain the Modified Observer’s Assessment of Alertness and Sedation (MOAA/S) scale < 3. The primary outcome was rate of successful FB completed. Secondary outcomes were time metrics, hemodynamics, intubating conditions, oxygen saturation, coughing severity, number of remedies, total dose of fentanyl, RF, RT, and Dex, incidence of dreaming, patient and bronchoscopist satisfaction, willingness to repeat bronchoscopy, and adverse events. Results: The FB successful completion rate was 94.52% (95% CI: 89.20–99.90) in the RR group and 91.78% (95% CI: 85.30–98.20) in the DR group. Compared with patients in the DR group, the onset time, time to fully alert, and hospital discharge were all significantly shorter in the RR group (P < 0.01), and hemodynamics were more stable in the RR group. Intubating conditions, clinically acceptable intubating conditions, lowest oxygen saturation, coughing severity, consumption of fentanyl and RF, number of remedies, and patient and bronchoscopist satisfaction were similar between the groups (P > 0.05), as were demographic characteristics, incidence of dreaming, willingness to repeat bronchoscopy, and adverse events (P > 0.05). Conclusion: RT-RF has non-inferior efficacy, better time metrics and hemodynamic stability for outpatients undergoing FB than Dex-RF.